Micro-CT Analysis of Y-TZP Copings Made by Different CAD/CAM Systems: Marginal and Internal Fit - Rafaella Caramori Saab; Leonardo Fernandes da Cunha; Carla Castiglia Gonzaga; Amanda Mahammad Mushashe; Gisele Maria Correr (International Journal of Dentistry)
Purpose. The aim of the study was to measure the marginal and internal adaptation (MIA) of zirconia copings, made of 4 ceramic systems for CAD/CAM, using microcomputed tomography (micro-CT) technology. Material and Methods. Two identical stainless steel models were used, representing a preparation for full ceramic crown on a lower molar. The master models were then scanned for the production of copings from specific yttrium oxide partially stabilized tetragonal zirconia polycrystal ceramic blocks of each system (n=10): Cerec/inCoris Zi, Sirona; Cercon/Cercon base, Dentsply; Ceramill/Ceramill Zi, Amann Girrbach; and Lava/Lava Frame Zirconia, 3M ESPE. MIA was evaluated measuring 4 points as follows: marginal gap (MG), axial wall gap (AW), axio-occlusal angle gap (AO), and central occlusal area gap (CO). The data were statistically analyzed by ANOVA and Tukey’s test (α = 0.05). Results. The ceramic system Lava showed greater internal desadaptation (80.75 ± 22.69 µm) while CEREC presented the lowest values (49.92 ± 11.77 µm). There were significant differences between the measurement points evaluated. CO demonstrated the greater values (77.03 ± 22.61 µm). All marginal and internal adaptation values were considered clinically acceptable. Conclusion. It was concluded that there was an influence of the type of ceramic system in marginal and internal adaptation of copings in zirconia.